Systematic Country Diagnostic of Senegal - World Bank Group (World Bank, Dakar, 2018)
This SCD argues that, against a historical backdrop of lackluster economic growth and poverty reduction, Senegal has progressively achieved since 2010 a structural turnaround in its economic performance, based on enhanced international competitiveness and, incipient demographic transition, with tangible impacts on poverty.